Online Quizizz for Teaching Reading at Junior High School - Rafiqa, Rafiqa; Nurunnisaa Alimah A.; Muhammad Danial (LETS: Journal of Linguistics and English Teaching Studies, 2024)
This study aimed to determine the effectiveness of using Quizizz in teaching reading in English subjects and to determine students' perceptions of using the application in learning. The study was conducted in SMP Negeri 3 Majene and used a quantitative method with a quasi-experimental design. The population in this study were all eighth-grade students of SMP Negeri 3 Majene. The sampling technique used Cluster Sampling by selecting two classes representing the entire population with 30 students in each group. Research data were collected through test and non-test instruments given to students using pre-test, post- test, and student perception questionnaires. The mean score for the pre-test for the Experiment Group was 66.90, while the average score for the post-test was 83.70. The research data were analyzed using parametric analysis as an Independent sample T-test, with the test results showing that sig. (2-tailed = 0.000) < 0.05. with the conclusion that the Quizizz application can be significantly used effectively in learning reading. As for the results of the student perception questionnaire, namely 88.35%, which is included in the good and positive categories. The conclusion is that Quizizz is more effective than conventional learning and is considered good for English learning.